2018
DOI: 10.7209/tanso.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of nitrogen-doped carbons prepared by the thermal reduction of furfurylamine-intercalated graphite oxide

Abstract: Nitrogen-doped carbons were prepared by the thermal reduction of furfurylamine-intercalated graphite oxide. The nitrogen atom content in the resulting samples was around 6 wt% and was almost constant, independent of the thermal reduction temperature. The nitrogen atoms were introduced in the forms of pyridinic, pyrrolic and graphitic, and the amount of graphitic nitrogen greatly increased for the sample prepared at 800 °C. The discharge capacity above 1.0 V greatly decreased for nitrogen-doped carbon samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For the last issue, the structural changes of GLG during intercalation of lithium ions would be important. We have reported that lithium ions are intercalated into it at a higher cell voltage of 0.48 V and the interlayer spacing reached a very large value of 0.48 nm at 0 V. We have also found that all of the lithium species stored in fully charged GLG are in the ionic state, based on the 7 Li NMR measurement. 5 However, the intercalation behavior of lithium ions into GLG especially at the early stages of it has not yet been studied, which would be strongly related to the formation of SEI.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…For the last issue, the structural changes of GLG during intercalation of lithium ions would be important. We have reported that lithium ions are intercalated into it at a higher cell voltage of 0.48 V and the interlayer spacing reached a very large value of 0.48 nm at 0 V. We have also found that all of the lithium species stored in fully charged GLG are in the ionic state, based on the 7 Li NMR measurement. 5 However, the intercalation behavior of lithium ions into GLG especially at the early stages of it has not yet been studied, which would be strongly related to the formation of SEI.…”
mentioning
confidence: 65%
“…[5][6][7] They are denoted as GLGT (T; heat-treatment temperature). Air treated GLG800 obtained in our previous study 5 was also used and was denoted as A-GLG800.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, our group has proposed a new carbon-based anode material named graphene-like graphite (GLG). GLG is synthesized via the thermal treatment of graphite oxide (GO) under a vacuum. In this process, the expanded interlayer distance of GO decreased, and the resulting GLG shows almost the same interlayer distance as that of graphite.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have recently introduced graphene-like graphite (GLG) as a new candidate for an anode material of LIBs, which can overcome these intrinsic difficulties of the carbon-based materials. [7][8][9][10] The capacity of GLG reaches 608 mAh g ¹1 with a cutoff voltage of 2 V, and it shows good cycle performance. In addition, the rate capability of GLG is superior to that of graphite; the capacity of GLG at 6 C remains 79% of the capacity at 0.1 C. GLG is synthesized via thermal reduction of graphite oxide (GO) under vacuum with quite small increasing-rate of temperature to avoid exfoliation of graphene sheets.…”
Section: Introductionmentioning
confidence: 99%